PERSEPSI ANAK SEKOLAH DASAR TENTANG PERILAKU MEROKOK PADA SISWA SD NEGERI GROGOL 05 KOTA JAKARTA BARAT - Nurapipah; Nurul Febrianti (STKIP Subang, 2023)
This research was conducted with the aim of knowing the perceptions of elementary school children on smoking behavior in Grogol 05 State Elementary School students in West Jakarta in grades 5 A and B with a total of 52 students. This research is a descriptive quantitative study using a frequency distribution method. Data collection techniques in the form of closed questionnaires or questionnaires. The results of the study found that the majority of Grogol 05 Elementary School children's perceptions were